FRI0383 Detect screening for pulmonary arterial hypertension in systemic sclerosis: data from an eustar cohort. (15th June 2017) - Ancuta, C; Pomirleanu, C; Maxim, R; Mitu, F
Abstract : Background: Early documentation of pulmonary arterial hypertension (PAH) related to systemic sclerosis (SSc) remains a challenge in daily clinical practice, with major prognostic and therapeutic implications. Although several screening algorithms specifically designed to optimize the detection of secondary PAH have already been proposed (e.g., DETECT, REVEAL), no precise approach received complete validation, especially the use of invasive diagnostic right heart catheterization (RHC). Objectives: Main objective was to assess the risk of PAH in patients with SSc and to compare with PAH screening promoted by European Society of Cardiology/ European Respiratory Society (ESC/ERS) 2009 guidelines, while secondary one to identify predicting factors for developing PAH among clinical and immunological SSc variables. Methods: Cross-sectional prospective single-center study, applying the DETECT calculator in patients with SSc recruited in EUSTAR 162 center cohort between January 2013- December 2016; all SSc completing at least two monitoring visits at 6 months were considered. Standard assessments included MEDS (minimal data set EUSTAR), annual echocardiography with systolic pulmonary artery pressure (sPAP), pulmonary function tests with forced vital capacity (FVC), percentage predicted/diffusing capacity for carbon monoxide (DLCO) % predicted, ECG, serum biomarkers (serum urate, NT-proBNP). PAH risk calculator (http://detect-pah.com/pah-risk-calculator), a tool developed and validated in the DETECT study, is able to identify patients requiring echocardiography (STEP 1) respectively RHC (STEP 2), and was systematically applied in our cohort. All sPAP ≥45 mmHg or between 35–45 mmHg in the presence of dyspnea were proposed for invasive testing. Statistical analysis was performed in IBM SPSS-19 version, p<0.05. Results: 41 out 56 SSc in our database were recruited: mainly women (85.36%) with diffuse cutaneous SSc (63.41%), anti-topoisomerase (up to half) and anti-centromere (about one third) positive disease; one out of four 4 SSc presented with digital ulcers and one of three with active capillaroscopic pattern. Using the DETECT PAH calculator, 14/ 41 (34.14%) were recommended for RH as follows: an initial value above 300 points in STEP 1 (with further indication of echocardiographic assessment) and subsequent STEP 2 over 35 were recorded. On the other hand, only 9/41 (21.95%) cases met the ultrasound criteria to be addressed to an invasive assessment when applying the ESC/ERS 2009 guidelines, the difference being statistically significant as compared to DETECT (p<0.05). PAH was finally confirmed in 8/41 (19.51%) cases, supporting our preliminary results in a pilot study on a limited number of patients. Conclusions: DETECT is a reliable algorithm for early detection of PAH in patients with SSc, optimizing PAH screening and prompting the rheumatologist-cardiologist collaboration. Disclosure of Interest: None declared